Factors influencing the level of satisfaction on online learning among tertiary students during Covid-19 pandemic era – a Malaysian study - Soliha Sanusi,; Nik Herda Nik Abdullah,; Nabilah Rozzani,; Muslichah, Istyakara (Penerbit Universiti Kebangsaan Malaysia, 2022)
The rapid progression for online learning today has turned into something even more significant with the Covid-19 pandemic, which had forced many schools worldwide to be closed for physical interactions. Education providers since then have been forced to push forward with the integration of online learning as an alternative to the blackboard-style of learning. From being complementary, online learning has now become the main medium of delivery for both teaching and learning for education providers at various levels, including universities. Lecturers and students on tertiary education levels were subconsciously forced to engage with synchronous and asynchronous activities on online platforms. As such, this study examines the higher learning institution students’ preparedness, motivation, internet availability, technical support and psychological support that influences students’ online learning satisfaction in Malaysia. Three hundred and thirty-six (336) responses were collected via online survey across Malaysia within three months from December 2020 until February 2021. Smart PLS 3.2.4 was used with Structural Equation Model for data analysis, with five hypotheses being examined for the current study. Findings from the current study demonstrated that motivation, psychological support, and technical support had significantly affected students’ satisfaction. The outcomes of this study contributed to current trend of research during Covid-19 pandemic, which had placed particular focus on online learning. The current study was developed as there were only a few research that had been performed on this subject matter, particularly within a Malaysian context. It was suggested from findings of the current study that future studied can compare different countries to understand what whether similar factors that might have contributed to students’ online learning satisfaction in the higher learning institutions can be found in multiple countries.